Analyzing the Major Failures and Key Risks Linked to Dental Fixed Prostheses: An in Vivo Clinical Study - Saleha Alalwani; Seham Elsawaay; Ahmed Mhanni (AlQalam Journal of Medical and Applied Sciences, 2024)
This clinical investigation aimed to identify factors leading to fixed partial denture failures and their implications, crucial for enhancing clinical outcomes. Conducted in Tripoli, Libya, with 75 patients contributing 235 units, the study utilized John F. Johnston’s and John J. Manappallil’s classifications to categorize failure causes. Mechanical issues, predominantly in female patients, were identified as the primary cause of dental bridge failure, particularly in porcelain fused to metal (PFM) bridges with a "Fixed-Fixed" design, mostly in the upper jaw. The study underscores the importance of a multifactorial approach in preventing and managing fixed partial denture failures, emphasizing meticulous prosthesis design, manufacturing, and placement, alongside patient selection, diagnosis, treatment planning, and oral hygiene education. يهدف هذا التشخيص السريري الي تحديد العوامل التي تؤدي الي فشل التركيبات السنية الثابتة وآثارها، وهو أمر بالغ الأهمية لتعزيز النتائج السريرية. أُجريت هذه الدراسة في طرابلس، ليبيا، بمشاركة 75 مريضاً لديهم 235 وحدة، واستخدمت تصنيفات كلا من: جون إف جونستون وجون جيه ماناباليل لتحديد أسباب فشل التركيبات الثابتة. وجدت الدراسة ان أكثر المشاكل هي ميكانيكية، اغلبها عند المرضي الاناث كانت السبب الرئيسي لفشل جسر الاسنان، معظم التركيبات الفاشلة كانت في الجسور الخزفية المندمجة مع المعدن (PFM) ذات التصميم " الثابت - الثابت"، ومعظمها في الفك العلوي. تؤكد الدراسة على أهمية اتباع نهج متعدد العوامل في منع وإدارة فشل تركيبات الاسنان الثابتة، مع التركيز على التصميم والتصنيع ومكان وضع التركيبة، إلى جانب اختيار المريض والتشخيص وتخطيط العلاج والتثقيف حول نظافة الفم.